Changes in the Czech wage structure: Does immigration matter? - Kamil Dybczak; Kamil Galuščák (European Central Bank (ECB), 2010)
Using the Albrecht et al. (2003) version of the Machado and Mata (2005) decomposition technique along the wage distribution, we find that immigrant workers do not affect changes in the Czech wage structure between 2002 and 2006 despite their substantial inflows. Instead, changes in the wage structure are explained solely by increasing returns of native workers, while changes in the observed characteristics of native workers, particularly a rising level of education, are responsible for increasing wage dispersion. The sizeable inflows of foreign workers in the sample years are concentrated among young workers with primary and tertiary education and are primarily due to rising labour demand. The negative immigrant-native wage gaps are persistent along the wage distribution and are explained mainly by differences in observed characteristics. We provide evidence on increasing returns to education of native workers along the wage distribution. The returns are higher in 2006 than in 2002, in line with the evidence in the previous literature.
Keywords: J31; J21; 330; immigration; matched employer-employee data; quantile regression; wage gap decomposition; Wage Structure; Lohnstruktur; Lohnstruktur; Einwanderung; Arbeitsmigranten; Tschechien